Single Platinum Atom Doping to Silver Clusters Enables Near‐Infrared‐to‐Blue Photon Upconversion. (12th January 2021) - Niihori, Yoshiki; Wada, Yuki; Mitsui, Masaaki
Abstract: Photon upconversion (UC) from near‐infrared (NIR) to visible has been realized using singlet‐to‐triplet absorption of sensitizers, which are currently limited to osmium complexes and semiconductor nanocrystals. Motivated by the atomically precise tunability of electronic structure and photophysical properties of noble metal clusters, which often possess absorption bands that extend into the NIR region, we investigated MAg24 (SR)18 (M=Ag, Pt; SR=2, 4‐dimethylbenzenethiolate) clusters as a new NIR‐absorbing sensitizer for triplet–triplet annihilation UC. Combined with a blue light emitter, the NIR excitation ( λ ex =785 nm) of Ag25 (SR)18 results in no UC emission, while PtAg24 (SR)18 exhibits strong UC emission. This enhancement is primarily due to a significant increase in the intersystem crossing quantum yield of the cluster associated with the spin–orbit coupling enhancement in the M@Ag12 core. Abstract : PtAg24 (SR)18 (SR=2, 4‐dimethylbenzenethiolate) clusters serve as a new NIR‐absorbing sensitizer for photon upconversion via triplet‐triplet annihilation. Furthermore, Pt‐doping significantly increases the intersystem crossing yield of the cluster through spin–orbit coupling enhancement in the M@Ag12 icosahedral core.